Large non-functioning substernal parathyroid cyst: A case report and review of the literature. (April 2022) - Diaz, Ashley; Chavez, Julia; Hemmrich, Maximilian; Smith, Heather; Donington, Jessica S.; Portugal, Louis G.
Abstract: Objectives: Parathyroid cysts are rare benign lesions of the head and neck that account for less than 1% of cystic neck masses. We present a rare case of a large 6 cm substernal parathyroid cyst. Presentation of case: An otherwise healthy 65 year-old female presented to the otolaryngology clinic for evaluation of an anterior, midline neck mass. On physical exam, she was noted to have a fullness in the anterior neck extending to the sternal notch. CT demonstrated an enlarged thyroid with a cyst extending to the aortic arch. Initial evaluation suggested a bilateral goiter with substernal extension. The cyst was managed with drainage and observation. After two years of continued growth, the patient underwent a left thyroid lobectomy and mediastinal mass resection via the cervical approach. Final pathology was consistent with a parathyroid cyst. Conclusions: Parathyroid cysts are a rare cause of neck mass in an adult, and a 6 cm substernal parathyroid cyst represents an unusual site and size for these cysts. Parathyroid cysts are not often considered on the differential of neck and mediastinal cystic lesions. However, appropriate steps should be taken to ensure a proper diagnosis for any cystic lesion in the neck. Highlights: Parathyroid cysts are rare benign lesions of the head and neck A 65 year-old female with a 6cm cystic neck mass extending to the aortic arch. A mediastinal mass resection showed pathology consistent with a parathyroid cyst. Parathyroid cysts are not often considered on the differential of mediastinal cystic lesions.